Single-Cell Data and Weighted Correlation Network Analysis Revealed the Regulatory Mechanisms of Macrophages in Carotid Plaques - Yakun Ding; Xiaoyang Niu; Peng Guo; Bing Wang (Journal of Immunology Research, 2025)
Conclusion: This study discovered potential biomarkers that affected carotid plaque progression and macrophage regulation at the single-cell level, and examined their regulatory roles in immune regulation, programed cell death (PCD), and inflammatory factor modulation.